Head-to-head comparison of proprietary PPG and single-lead ECG algorithms for atrial fibrillation detection. (24th May 2021) - Gruwez, H; Evens, S; Proesmans, T; Smeets, C; Haemers, P; Pison, L; Vandervoort, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Population based screening for atrial fibrillation (AF) has been suggested to reduce stroke. Photoplethysmography (PPG) deriving smartphone apps and single-lead electrocardiography (ECG) tools are attractive devices for screening due to their low cost, convenience, and accessibility. Automated algorithm analysis can serve as pre-screening or remote monitoring for AF, while confirmation on an ECG trace >30s is required to establish the diagnosis. This work directly compares the performance of proprietary algorithms on PPG vs single-lead ECG for the detection of AF. Purpose: To evaluate and compare the diagnostic performance of a PPG-deriving smartphone app and a single-lead ECG-deriving handheld device for AF detection. Methods: Patients were recruited from the cardiology ward. After obtaining written informed consent, demographic and medical information were collected. Patients were instructed to perform one measurement using a pulse-deriving smartphone app and one via a single-lead ECG handheld device. A 12-lead electrocardiogram (ECG) was collected and interpreted by a cardiologist as gold standard. Patients with atrial flutter were excluded, with additional exclusions for insufficient quality measurements and unsuccessful measurements resulting due to technical errors. Unclassified single-lead ECG measurements were handled as test-negative. Sensitivity, specificity and accuracy were calculated with respect to the reference diagnosis. McNemar's analysis was performed to compare the sensitivity and specificity of the proprietary PPG and single-lead ECG AF detection algorithms. Results: The median age in the study population (n = 300) was 70 years (interquartile range: 51-78), 56.3% were men, and the median CHA2DS2-VASc was 3 (interquartile range: 1-4) with an AF-prevalence of 32.3%. PPG signal and single‑lead ECG quality was sufficient in 272/300 (91.0%) and 278/298 (93.3%) participants, respectively. After excluding atrial flutter patients (n = 25) and insufficient quality measurements, the sensitivity and specificity were 97.6% (95% CI 93.8 to 99.3) and 94.1% (95% CI 86.8 to 98.1) for the PPG signal versus 95.7% (95% CI 91.4 to 98.3) and 91.1% (95% CI 83.2 to 96.1) for the single‑lead ECG signal, respectively. Results demonstrated a 96.4% (95% CI 93.2 to 98.3) accuracy for PPG and 94.1% (95% CI 90.4 to 96.6) for single-lead ECG. No significant differences in sensitivity (P = 0.453) or specificity (P = 0.219) between the proprietary PPG and single-lead ECG algorithms were found. Conclusion: This study demonstrated equivalent diagnostic performance of PPG and single-lead ECG proprietary AF detection algorithms in smartphone apps.